Biosorption of Ranitidine Onto Live Activated Sludge - Savci, Serpil (Asian Journal of Chemistry, 2013)
Ranitidine is a drug responsible for disturbing the microbial ecology of surface waters. The potential use of live activated sludge (0.5 g and 1.0 g) for removal of ranitidine, one of the most widely used H2-receptor antagonists, from aqueous solution was examined. The biosorption of ranitidine on live activated sludge was investigated in a batch system. The ranitidine biosorption was fast and equilibrium was attained within 10 min. Data obtained from batch studies applied to Langmuir, Freundlich, Tempkin isotherm models. Kinetic and equilibrium adsorption data show that the process obeys to the pseudo-second order kinetic equation, Freundlich and Tempkin adsorption models. Gibbs free energy values were found to be 4.588 kj/mol for 0.5 g adsorbent and 3.613 kj/mol for 1.0 g adsorbent and indicating the not spontaneity of the system. Octanol-water partition coefficient (Kow) and biosorption coefficient, Kd, which describes the solid liquid partitioning characteristics of a compound in biosorption mechanism were also calculated.